(untitled) (BIOM - Revue scientifique pour la biodiversité du Massif central, 2022)
Riparian corridors are the most diverse and complex habitats in the world, the site of many processes essential to maintaining water quality and biodiversity. Diptera, the second largest group of insect species in the world, have ecological requirements that can express the complexity of riverine habitats and subsurface water exchanges. Moreover, they are the most abundant and diverse group in our river corridors. They therefore occupy a major role in the food webs of rivers and riparian terrestrial ecosystems. A rapid sampling method of riverine or aquatic Diptera imagos was applied on 11 stations, including 5 in the Massif central, while the quality of their river corridor was characterised using the IBCR index. The relationships between dipteran communities and riparian corridor characteristics were analyzed. For this, I used a traditional taxonomic approach and a functional approach based on the ecological traits of their larvae (feeding and water affinity). 252 dipteran taxa, including seven dipteran species cited for the first time in France, were identified. The climate, the state of conservation and the flow diversity of the streams in the Puy-de-Dôme seem to be particularly favourable for the communities of riverine Diptera. Our results indicate that an older, wider river corridor with river dynamics favoring a complex mosaic of habitats hosts a greater diversity of species and larval feeding modes and water affinities. In addition, the sampling of dipterans gives indications on the carrying capacity of marginal habitats, making it possible to better valorize hydromorphological restorations.